Integration of Digital Technology in Financial and Account-ing Systems and Its Implications for the Quality of Deci-sion-Making - Elexsi Yosefina Budiyon Poyk; Mikhael Manek; Christiana Wahyuningrum; Tri Suris Lestari (Digital Innovation : International Journal of Management, 2026)
The rapid advancement of digital technology has transformed financial and accounting systems, enabling organizations to process information more efficiently and support data driven decision making. However, the extent to which this integration improves the quality of decision making remains conceptually diverse in existing studies. Therefore, this study aims to analyze the integration of digital technology in financial and accounting systems and its implications for the quality of decision making. The research method used is qualitative with a literature review approach, involving a sample of 30 scientific articles published between 2018 and 2026 from reputable international journals. Data were collected through document analysis and examined using thematic analysis techniques, including data reduction, categorization, and interpretation. The findings indicate that digital technology significantly enhances decision making quality through improved accuracy, timeliness, and analytical capability of financial information. Nevertheless, the effectiveness of this integration is influenced by organizational readiness, digital literacy, and system alignment. The study concludes that digital technology acts as a strategic enabler in decision making processes when supported by competent human resources and effective implementation strategies.